2020
DOI: 10.1021/acs.jafc.0c04974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Flavonoids on Dipeptidyl Peptidase-IV Activity and Expression: Insights into Structure–Activity Relationship

Abstract: The inhibitory effects of 30 dietary flavonoids on dipeptidyl peptidase-IV (DPP-IV) were investigated to illustrate their quantitative structure−activity relationship (QSAR) and further explore their inhibition at the cellular level. Results of in vitro experiment show that isorhamnetin-3-O-glucoside (IC 50 , 6.53 ± 0.280 μM) had the strongest inhibition followed by cyanidin-3-Oglucoside (IC 50 , 8.26 ± 0.143 μM) and isorhamnetin-3-O-rutinoside (IC 50 , 8.57 ± 0.422 μM). A 3D QSAR model [comparative molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…The IC 50 values of these flavonoids were determined to be 138.79 ± 0.87 μM, 156.29 ± 1.18 μM, 166.52 ± 0.6 μM, 81.05 ± 4.14 μM, and 149.96 ± 0.58 μM, respectively. Gao et al ( 34 ) also reported a strong inhibitory activity of cyanidin 3-O-glucoside against DPP-4 with a IC 50 value of 8.26 μM in their experiments. The difference in the IC 50 value might be owing to the use of different DPP-IV inhibitor screening assay kit, in which the origin of DPP-4, concentration of the enzyme and substrate may be different from each other, and thus leading to differences in the obtained results among different researches.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The IC 50 values of these flavonoids were determined to be 138.79 ± 0.87 μM, 156.29 ± 1.18 μM, 166.52 ± 0.6 μM, 81.05 ± 4.14 μM, and 149.96 ± 0.58 μM, respectively. Gao et al ( 34 ) also reported a strong inhibitory activity of cyanidin 3-O-glucoside against DPP-4 with a IC 50 value of 8.26 μM in their experiments. The difference in the IC 50 value might be owing to the use of different DPP-IV inhibitor screening assay kit, in which the origin of DPP-4, concentration of the enzyme and substrate may be different from each other, and thus leading to differences in the obtained results among different researches.…”
Section: Resultsmentioning
confidence: 83%
“…These results also confirmed the importance of hydroxyl groups on DPP-4 inhibition of flavonoids and indicated that methylation of the hydroxyl groups on ring A and B is not favorable for the DPP-4 inhibition of flavonoids. Gao et al also found methylation of the hydroxyl group at position 4' of ring B led to weaker inhibitory activity against DPP-4 by comparing the inhibitory activity of eriodictyol and hesperitin ( 34 ). Nontheless, methylation of the hydroxyl group at position 3 of ring C tended to improve the inhibitory effect as evidenced by comparing the inhibitory activity of quercetin (E23) with 3-O-methylquercetin (E22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we found that apigenin-7- O -glucoside (A7G), isorhamnetin-3- O -rutinoside (I3R), and cyanidin-3- O -glucoside (C3G) were the three most effective flavonoids for inhibiting the activities of α-glucosidase and dipeptidyl peptidase-IV and improving insulin resistance among more than 20 dietary flavonoids that may be beneficial for diabetic patients in controlling blood glucose [ 12 , 13 ]. However, information about the effects and mechanisms of the three flavonoids on AGEs-induced inflammation and vascular endothelial dysfunction remain unknown.…”
Section: Introductionmentioning
confidence: 99%